2017
DOI: 10.1002/2017jb014464
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Dependent Elastic and Transport Properties of Porous and Permeable Rocks: Microstructural Control

Abstract: Although several studies aimed at linking electrical and hydraulic transport properties in rocks, the existing models remain at most incomplete. Based on this observation, in addition to the transport properties, this contribution investigates the pressure dependence of P wave velocities and porosity for three porous rocks. Apart from hydraulic conductivity, all physical properties show an important dependence to the confining pressure. In particular, electrical resistivity reaches an asymptote at low confinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
4
19
0
Order By: Relevance
“…In practice, the concept of transient permeability introduces a theoretical challenge in modeling magmatic systems, since both the spatial and temporal scales at which permeability is being enhanced and subsequently reduced are small compared to those for magma reservoir evolution (millimeter‐centimeter scale vs. kilometer scale; days‐years compared to thousand years‐million years). Additionally, the permeability is a function of not only the porosity of the medium but also the pore geometry (size, connectivity, and crack shapes), alteration, multiphase fluid properties, temperature, and pressure (e.g., Burgisser et al, ; Colombier et al, ; Heap & Kennedy, ; Heap et al, , ; Kushnir et al, ; Parmigiani, et al ; Pimienta et al, ; Vasseur & Wadsworth, ). Consequently, variations in these properties lead to a multitude of mechanisms for both increase and decrease of transient permeability, some of which can be strongly nonlinear.…”
Section: Transient Permeabilitymentioning
confidence: 99%
“…In practice, the concept of transient permeability introduces a theoretical challenge in modeling magmatic systems, since both the spatial and temporal scales at which permeability is being enhanced and subsequently reduced are small compared to those for magma reservoir evolution (millimeter‐centimeter scale vs. kilometer scale; days‐years compared to thousand years‐million years). Additionally, the permeability is a function of not only the porosity of the medium but also the pore geometry (size, connectivity, and crack shapes), alteration, multiphase fluid properties, temperature, and pressure (e.g., Burgisser et al, ; Colombier et al, ; Heap & Kennedy, ; Heap et al, , ; Kushnir et al, ; Parmigiani, et al ; Pimienta et al, ; Vasseur & Wadsworth, ). Consequently, variations in these properties lead to a multitude of mechanisms for both increase and decrease of transient permeability, some of which can be strongly nonlinear.…”
Section: Transient Permeabilitymentioning
confidence: 99%
“…Further comparing formation factor‐to‐porosity (i.e., F ‐ϕ) variations with that reported in the literature (Figure b). Usual F ‐ϕ data sets aiming at the linking of the properties from varying one single parameter (e.g., pore size) investigate natural rocks that span porosities from 5% to about 30% (Lesmes & Friedman, ; Lesmes & Frye, ; Pimienta, Sarout, et al, ; Revil et al, , ; Titov et al, ; Tong et al, ; Weller et al, ). This new data set investigates specifically the effects of microcracks and evidences a change of slope in the F ‐ϕ trend for porosities below 5–7%, when compared to usual trends.…”
Section: Interpretationsmentioning
confidence: 99%
“…Permeability links directly to the rock porous network, in terms of its concentration and its connectivity (Bernabé, ; C. David et al, , ; Guéguen & Dienes, ; Pimienta, Sarout, et al, ; Sarout, ). Assuming simple geometries of either tubes (i.e., connected spherical pores) or penny‐shaped cracks, one could predict the permeability of a material.…”
Section: Interpretationsmentioning
confidence: 99%
“…Several theoretical studies have proposed empirical models to understand the temperature‐, pressure‐, and porosity‐dependent elasticity . To date, a number of experimental studies have reported the validation of the above theoretically proposed models …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] To date, a number of experimental studies have reported the validation of the above theoretically proposed models. [17][18][19][20][21][22] However, there is a limited literature on experimental studies which characterize the influence of the pore-saturated fluid and its pressure on the elasticity of porous specimens. This work seeks to use resonant ultrasound spectroscopy (RUS) to experimentally illustrate the effects of saturated fluid properties on the elasticity of the porous material.…”
Section: Introductionmentioning
confidence: 99%